Analisis Pembinaan Prestasi SSB Kelompok Umur 14 Tahun Se-Kecamatan Tahunan - Firman Maulana; Setiyawan Setiyawan; Yulia Ratimiasih (Journal of Physical Activity and Sports (JPAS), 2020)
This research is motivated by the results of observations made by researchers related to the development of SSB achievements of the 14 year age group in the annual sub-district, from the number of SSB groups aged 14 years that are formed in this annual sub-district, the problem in this study is that the contribution of athletes is very less than each. SSB, and funding sources are still lacking. In this study using qualitative descriptive naturalistic methods. The population in this study was SSB in the annual sub-districts while the sampling technique used was purposive sampling. Data collection techniques using interviews, observation, and documentation. The validity of the data using triangulation techniques. Data analysis with data collection, data reduction, data presentation, and drawing conclusions. The results of the research that have been carried out are that, 1) the establishment of SSB as a sub-district aims to provide a platform for channeling football talent, 2) organizational management is carried out in moderation, 3) athlete nurseries are good, 4) coaches are good 5) the implementation of the training program is good, 6) the funding is quite good, 7) the facilities and infrastructure owned are sufficient, 8) the achievement is good. From the data obtained, it can be concluded that the coaching of achievements in the annual districts has been going well. The suggestions given by the researchers were 1) the management should be more serious in managing the SSB organization, 2) the funding process must run well, the management and management must allocate funds as well as possible. Keywords: Analysis, Achievement Development, SSB, Age 14 Years Abstrak Penelitian dilatarbelakangi dari hasil observasi yang dilakukan oleh peneliti terkait dengan  pembinaan prestasi SSB kelompok umur 14 tahun se-kecamatan Tahunan, dari banyaknya SSB kelompok umur 14 tahun yang terbentuk se-kecamatan Tahunan ini, permasalahan dalam penelitian ini adalah kontribusi atlet yang sangat kurang dari setiap SSB, dan sumber pendanaan masih kurang. Dalam penelitian ini menggunakan metode kualitatif deskriptif naturalistik. Populasi dalam penelitian ini adalah SSB se-kecamatan Tahunan sedangkan teknik pengambilan sampel yang digunakan  yaitu purposive sampling. Teknik pengumpulan data dengan menggunakan metode wawancara, observasi, dan  dokumentasi. Validitas data dengan teknik triangulasi. Analisis data dengan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan.  Hasil penelitian yang telah dilakukan bahwa, 1) pendirian SSB se-kecamatan bertujuan untuk memberikan wadah untuk  menyalurkan bakat sepakbola, 2) pengelolaan organisasi dijalankan seadanya, 3) pembibitan atlet sudah baik, 4) pelatih sudah baik. 5) pelaksanaan program latihan sudah baik, 6) pendanaan cukup baik,7) sarana dan prasarana yang dimiliki sudah cukup memadai,8) prestasi baik,. Dari data yang diperoleh dapat disimpulkan bahwa, pembinaan prestasi se-kecamatan Tahunan sudah berjalan baik. Saran yang peneliti berikan, 1) hendaknya pengurus lebih serius dalam melakukan pengelolaan organisasi SSB, 2) proses pendanaan harus berjalan dengan baik, pengurus maupun manajemen harus mealokasikan dana sebaik mungkin.   Kata kunci: Analisis, Pembinaan Prestasi, SSB, Umur 14 Tahun